Effectiveness and Safety of Palivizumab for the Prevention of Serious Lower Respiratory Tract Infection Caused by Respiratory Syncytial Virus: A Systematic Review - Gonzales, Tara; Bergamasco, Aurore; Cristarella, Tiffany; Goyer, Camille; Wojdyla, Matthew; Oladapo, Abiola; Sawicky, John; Yee, John; Moride, Yola (American Journal of Perinatology, 2023)
Objective Palivizumab is a humanized monoclonal antibody approved for the prevention of serious lower respiratory tract infection (LRTI) caused by respiratory syncytial virus (RSV) in infants and young children at high risk of RSV disease. This systematic review summarized evidence on the effectiveness and safety of palivizumab when used in approved populations.Study Design A systematic review of Phase III trials and observational studies was conducted according to the population, intervention, comparator, outcome, timing, setting (PICOTS) approach (PROSPERO, CRD42021281380). Target populations consisted of infants with a history of premature birth (≤35-week gestational age) and children aged <2 years with bronchopulmonary dysplasia (BPD) or with hemodynamically significant congenital heart disease (hs-CHD). Outcomes of interest included RSV-related hospitalization, admission to intensive care unit (ICU), requirement for mechanical ventilation, treatment-related adverse events (AEs), and RSV-related deaths. Information sources were literature search (Ovid MEDLINE and Embase), pragmatic searches, and snowballing (covering the period up to 07 September 2021).Results A total of 60 sources were included (5 Phase III trials and 55 observational studies). RSV-related hospitalization rates following palivizumab prophylaxis in Phase III trials were 1.8% in premature infants and 7.9% in children with BPD, which were significantly lower than rates in placebo arms. In the real-world setting, similar hospitalization rates were found (0.7–4.0% in premature infants [16 studies] and 0–5.5% in patients with BPD [10 studies]) with ICU admission reported in 0 to 33.3% of patients hospitalized for RSV. In Phase III trials, RSV-related mortality rates were 0.2 and 0.3%, while AEs occurred in 11% of premature and/or BPD patients and 7.2% of hs-CHD patients, consisting mainly of injection site reaction, fever, and diarrhea. Similar results were found in observational studies.Conclusion This systematic review supports the effectiveness and safety of palivizumab in the indicated populations.Key Points
Keywords: systematic review; respiratory syncytial virus; palivizumab; efficacy; effectiveness; safety